ANALISIS TINDAKAN WARGA DESA PAYAMAN DALAM MENCEGAH PENYAKIT DBD - Didi Intan Pratiwi; Rachmat Hargono (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2017)
Dengue Hemorrhagic Fever (DHF) is caused by dengue virus carried by Aides Aigepty mosquitoes. Since 2015 there has been a typical DHF in Payaman Village as 3 people and one of them was died in 2016. One typical of DHF has been an Extraordinary Occurrence in the health sector. One that can trigger dengue disease is the low rate of larvae free. Eradication of DHF can be done with Mosquito Nest eradication activity. In this study aims to analyze the actions of villagers who can trigger dengue disease and actions that can prevent dengue disease. The research method used is descriptive quantitative. Data source used is primary data and secondary data. Primary data was collected by interviewing questionnaires in each house. To support the completeness of the data used qualitative methods by conducting in-depth interviews on various related sectors. Secondary data is taken from Payaman Village Dasawisma data and Village Profile data. The results of the study found that the villagers of Payaman, especially RT 15-22 have acts that can trigger dengue fever, such as the handling of late dengue cases, not drain the water reservoir, poor waste management of households, the management of used less precise and laying the animal cage inside the house. While the actions that can be used to prevent dengue fever is using mosquito nets when sleeping and keep fish in water reservoirs. It needs to be improved by changing actions that can trigger dengue disease into actions that can prevent dengue disease that drains the water reservoir, manages household waste well, manages the used goods in the right way and puts the animal cage outdoors. In addition, dengue fever can be prevented by eradicating mosquito breeding and preventing mosquito bites. Growing mosquito breeding and preventing mosquito bites can be done with 3M plus movement.Keywords: dengue fever, payaman village, citizen action, 3M plus